2014
DOI: 10.5897/jphe2013.0596
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude to hypertension and lifestyle habits of rural dwellers in Owerre-Nkwoji, Imo State Nigeria

Abstract: Hypertension accounts for 13% of global mortality, with 25% prevalence in Nigeria. Current trends in management is lifestyle modification. Information on lifestyle habits is needed for effective intervention programe. A study was done among rural dwellers between ages 20 and 75 in Owerre-Nkwoji, Imo State, to determine their knowledge, attitude to hypertension and lifestyle habits. Information gathered would be used to plan an intervention programe to increase awareness and promote healthy lifestyles. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 4 publications
4
15
1
Order By: Relevance
“…High awareness and negative perception was same with the studies by Ekwunife (2010) and Osuala, Oluwatosin, and Kadiri (2014). Even in the Western part of the country, myths about cancer which is also a non communicable disease was recorded by Adedemeji, Lounsbury, Popoola, Asuzu, Lawal, Oladoyin, et al in their study in Ibadan.…”
Section: Discussionsupporting
confidence: 59%
“…High awareness and negative perception was same with the studies by Ekwunife (2010) and Osuala, Oluwatosin, and Kadiri (2014). Even in the Western part of the country, myths about cancer which is also a non communicable disease was recorded by Adedemeji, Lounsbury, Popoola, Asuzu, Lawal, Oladoyin, et al in their study in Ibadan.…”
Section: Discussionsupporting
confidence: 59%
“…It is also in line with the findings of studies conducted by researchers in Nigeria, Africa and America. In the study by Osuala et al responses on awareness of incidents of stroke and sudden deaths in the community was 88 (73.3%) each while average knowledge was 40 (33.3%) [13]. Ike et al stated that 50% of their patients thought that hypertension was caused by stress [14].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension in Nigeria with a population of 1 million [11] was between 20% and 25% according to Danbauchi [8]. However a study in Port Harcourt, South-South of Nigeria reported a prevalence of 40.82% among the study participants [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension if left unchecked especially in the rural area where the population is predominantly that of old people, would increase its incidence, cases of stroke, heart failure, glaucoma and renal failure. Even though many studies had been conducted on hypertension in various continents as Asia, America, and Africa by researchers [6][7][8]; only a few had been done in the rural area of Nigeria [9][10][11][12][13]. Isunjaba of Isu Local Government Area in Imo State being a rural community is not excluded.…”
Section: Introductionmentioning
confidence: 99%